(untitled) (Unizik Journal of Chemical and Environmental Engineering, 2026)
The quest for eco-friendly, cost-effective, and sustainable corrosion control solutions has intensified due to environmental concerns associated with synthetic inhibitors. This study investigates the inhibitory performance of ethanolic extract of soursop (Annona muricata) leaves on mild steel corrosion in potassium hydroxide (KOH) medium. Qualitative phytochemical analysis revealed the presence of alkaloids, flavonoids, tannins, terpenoids, saponins, cardiac glycosides, and anthraquinones compounds rich in heteroatoms (nitrogen and oxygen) and π-electron systems. FTIR spectroscopy confirmed O–H (3406 cm⁻¹), C=O (1718 cm⁻¹), C=C (1636 cm⁻¹), and C–O/C–N (1066–1245 cm⁻¹) functional groups. Weight loss measurements (triplicate, n=3) demonstrated that inhibition efficiency (IE) increases with longer immersion time (14.19- 68.17%), higher temperature (8.20-74.83%), increased alkaline concentration (19.72-57.19%), higher extract concentration (26.73-61.36%), and larger media volume (30.29-67.29%). Electrochemical impedance spectroscopy (EIS) revealed that charge transfer resistance (Rct) increased from 124 ± 8 Ω·cm² (uninhibited) to 482 ± 20 Ω·cm² (5% v/v extract), corresponding to IE of 74.3%. Potentiodynamic polarization showed mixed-type inhibition with cathodic predominance (IE = 76.2% at 5% v/v extract). Adsorption followed the Langmuir isotherm (R² > 0.99), with ΔG°ads values ranging from −35.2 to −42.1 kJ·mol⁻¹, confirming chemisorption. Activation energy increased from 28.4 kJ·mol⁻¹ (uninhibited) to 52.7 kJ·mol⁻¹ (inhibited). SEM revealed smoother surfaces (roughness reduced by 77%). All results were statistically significant (p < 0.05). This study establishes Annona muricata leaf extract as a promising, renewable, and highly effective green corrosion inhibitor for mild steel in alkaline environments.